Chinese nursing students' culture-related learning styles and behaviours: A discussion paper - Carol Chunfeng Wang; Kenneth Mark Greenwood (Elsevier, 2015)
Globalisation requires that nursing education focuses on culturally competent care. International students studying in Australia present a valuable resource for cultural learning, yet internationalisation presents opportunities and challenges for both lecturers and students. This paper explores Chinese nursing students, the single largest group of international students in Australia, their communication behaviour, patterns and learning styles at Australian universities from cultural and psychosocial perspectives. Our aim is to provide insight for educators in Western countries to better understand this particular ethnic group and help Chinese nursing students overcome learning difficulties and develop their potential learning capabilities. We further recommend coping strategies to help international Chinese nursing students' learning.